Efficiency of botanical extracts against Aphis craccivora Koch (Hemiptera: Aphididae) nymphs in Vigna unguiculata (L.) Walp - Dutra, Jefferson Auteliano Carvalho; Gomes, Victor Emmanuel de Vasconcelos; Bleicher, Ervino; Macedo, Deivielison Ximenes Siqueira; Almeida, Mirla Maria Mesquita (EntomoBrasilis, 2020)
The present study aimed to evaluate the insecticidal activity of hydroalcoholic plant extracts on Aphis craccivora Koch nymphs in cowpea. The experiments were carried out under greenhouse conditions in a randomized block design with five repetitions. Hydrated ethanol was used as a solvent in the botanical extract preparation. Cowpea plants were infested with five female adult aphids, eleven days after planting. After 48 hours, the adults were removed from the plants, leaving the recently bred nymphs. The evaluation of the nymphs’ survival was carried out forty-eight 48 hours after the application of the plant extracts. The botanical extracts with more than 50% efficiency were: Allium tuberosum leaf, Caesalpinia ferrea leaf, Piper aduncum leaf, Carica papaya seed, Dieffenbachia picta leaf, Cucurbita moschata seed and the control treatment, Annona squamosa seed. The botanical extracts with less than 50% efficiency were: Allium sativum bulb, Anacardium occidentale leaf, Borreria verticillata leaf plus flower, Coffea arabica leaf and seed, Delonix regia leaf and flower, Euphorbia tirucalli leaf, Leucaena leucocephala leaf, Mimosa caesalpiniaefolia leaf, Nerium oleander leaf, Syzygium cumini leaf, endocarp and pericarp, Syzygium malaccense leaf, Zingiber officinale rizome and Ziziphus joazeiro leaf. The highest efficiency levels were obtained by D. picta and C. moschata, rendering these extracts suitable for field trials to further evaluate their efficieny against the cowpea black aphid.